HALAL INDUSTRIES - Muhammad Aswad (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2022)
This article deals with the marketing strategies of halal certified products by Small and Micro Enterprises (SMEs) amid the rising middle-class Muslims in contemporary Java, Indonesia. These SMEs’ entrepreneurs compromise of the middle-class Muslims who are particularly concerned with fashion industries, snacks, and beverages with halal-certified label. Taking into account Benefit Opportunities Cost Risk (BOCR)-Analytic Network Process (ANP) as an approach, this article tries to identify both the proliferation of halal-certified products and the dominant mixed-factors in marketisation of halal products, including the marketing strategies used by SMEs. This article concludes that promotion—both conventional and digital—is widely essential, besides the product, price, and place aspects. Along with the rise of the middle-class Muslim in contemporary Indonesia, the commodification of religious symbols through halal-certification is one important factor that encourages the production of Muslim middle-class economy in contemporary Indonesia.